Pengaruh Konten Edukatif TikTok @sihoodiekuning terhadap Literasi Digital Mahasiswa Gen Z UNTAR - Syam, Sherly Oktaviani; Junaidi, Ahmad (Kiwari, 2025)
This study aims to analyze the influence of educational content from the TikTok account @sihoodiekuning on the digital literacy of Generation Z students at Tarumanagara University. The TikTok account @sihoodiekuning has garnered four hundred seventy-five thousand followers and millions of likes across its videos. As a popular social media platform among Generation Z, TikTok provides a space for creators like @sihoodiekuning to deliver relevant educational content. With an interactive visual approach, the content offered by this account includes tutorials, practical tips, discussions on social issues, and general knowledge. This account aligns with the needs of Generation Z students for informal learning and enchancing their digital literacy. The study adopts a descriptive quantitative approach with an online survey method. The sample comprises 50 respondents selected using purposive sampling techniques. Data were collected through an online questionnaire and analyzed using sample linear regression with SPSS software. The findings reveal a significant positive influence on students’ abilities to evaluate information, digital creativity, and communication skills. Educational content in the form of tutorials and practical tips was found to be the most effective in enchancing the digital literacy of Generation Z students. This research highlights the potential of TikTok as a relevant informal learning medium to support the digital literacy of younger generations. Penelitian ini bertujuan untuk menganalisis pengaruh konten edukatif dari akun TikTok @sihoodiekuning terhadap literasi digital mahasiswa Generasi Z Universitas Tarumanagara. Akun TikTok @sihoodiekuning memiliki jumlah pengikut yang mencapai empat ratus tujuh puluh lima ribu dengan jutaan likes pada berbagai videonya. TikTok sebagai platform media sosial yang popular di kalangan Generasi Z memberikan ruang bagi kreator seperti @sihoodiekuning untuk menyampaikan konten edukatif yang relevan. Dengan pendekatan visual yang interaktif, konten-konten yang disajikan oleh akun ini meliputi tutorial, tips praktis, diskusi isu sosial, hingga pengetahuan umum. Akun ini relevan dengan kebutuhan mahasiswa Generasi Z untuk belajar secara informal dan mengembangkan literasi digital yang lebih baik. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan metode survei online. Sampel terdiri dari 50 responden yang dipilih menggunakan teknik purposive sampling. Teknik pengumpulan data menggunakan kuesioner online dan dianalis dengan regresi linear sederhana memakai perangkat lunak SPSS. Hasil penelitian menunjukkan adanya pengaruh positif signifikan terhadap kemampuan mengevaluasi informasi, kreativitas digital, dan keterampilan komunikasi mahasiswa. Konten edukatif yang berbentuk tutorial dan tips dianggap paling efektif dalam meningkatkan literasi digital mahasiswa Generasi Z. Penelitian ini mengungkap potensi TikTok sebagai media pembelajaran informal yang relevan dalam mendukung literasi digital generasi muda.